Three-Year Outcomes of Patients with Neovascular Age-Related Macular Degeneration Treated with Aflibercept under the National Health Insurance Program in Taiwan - Kang-Jung Lo; Jin-Yu Chang; Hsin-Yi Chang; Shih-Hwa Chiou; De-Kuang Hwang; Shih-Jen Chen (Journal of Ophthalmology)
Purpose. To observe and analyze the long-term outcomes of patients with neovascular age-related macular degeneration (nAMD) treated with aflibercept monotherapy under the National Health Insurance (NHI) program in Taiwan. Methods. This retrospective observational study was conducted at Taipei Veterans General Hospital. Patients with naive nAMD who were treated with aflibercept and followed for more than 3 years were reviewed. The better eye was enrolled if both eyes were affected. Visual acuity (VA) and central macular thickness (CMT) were recorded for 3 years. The lost-to-follow-up rate, number of injections, and predictive factors for visual outcomes were analyzed. Results. Ninety-nine eyes in 99 patients were followed up for 3 years. The mean age at onset of nAMD was 82.8 ± 9.26 years, and 65% of the patients were male. Compared with initial visual acuity, 5 (5.1%) of our patients improved their vision for 3 or more lines after 3 years of follow-up, 11 (11.1%) of our patients improved for 1 to 3 lines, 62 (62.6%) patients remained their vision with 1 line or less changes, 15 (15.2%) patients lost their vision for 1 to 3 lines, and 6 (6%) patients lost their vision for 3 or more lines. The CMT was 359 ± 180 µm before treatment and 259 ± 98 after 3 years (p<0.001). The mean number of injections was 4.63 ± 1.91 in the first year, 2.13 ± 2.2 in the second year, and 1.42 ± 1.79 in the third year. Multivariate analysis showed that final VA was significantly associated with VA at year 1, the presence of retinal pigment epithelial detachment at year 1, and receiving more than four injections in the first year. Final CMT was only significantly associated with CMT at year 1. Conclusion. After 3 years of treatment under the NHI program in Taiwan, 21.2% of the patients with nAMD still had a visual decline despite good anatomical outcomes. More aggressive treatment or other strategies should be used for patients who may have a poor prognosis.